Spectral properties of a broadband far infrared photodetector with a new design of active region - M. V. Tkach; Ju. O. Seti; O. M. Voitsekhivska; V. V. Hutiv (Condensed Matter Physics, 2023)
A quantum theory of spectral parameters and oscillator strengths of quantum transitions in an active region, which contains cascades of wide quantum wells with a complicated potential profile is developed. A new spatial design of the cascade is calculated and proposed with such an asymmetric arrangement of the wells and barriers, in which, without an applied electric bias, the magnitudes of oscillator strengths are considerable and one-way resonant-tunneling transport of electrons is observed. As a result, it becomes possible to ensure a successful functioning of the broadband photodetector in the far IR range.